Synthesis of Guar gum Propionate Nanoparticles for Antimicrobial Applications. (2018) - Das, Aatrayee; Abdullah, Farooque; Kundu, Sonia; Mukherjee, Arup
Abstract: Biopolymer guar gum (GG) is available from the seed endosperm of annual legume plant Cyamopsis tetragonoloba. The surface exposed free hydroxyl groups in GG were decorated with propionate esters. The base catalyzed formylation reaction prompted introduction of propionate groups. The surfactant free water dispersible and self-assemble propionate nanoparticles were developed using a facile solvent-shifting method. The FTIR, XRD, 13 CNMR, DLS and TEM studies confirmed newly derivatized polymeric nanomaterial. The spherical shaped ouzo particles were effective for fungus and bacteria contact killing. This was considered due to the presence of high surface area and propionate moieties.